Optimized Three Level DC-DC Boost Converter using PID Controller - Mr. Divesh Kumar,Dr. Yogendra Narayan,Dr. Manish Gupta (International Journal of Advanced Science and Technology, 2020)
Voltage regulation of DC-DC multilevel boost converter is a very demanding issue as Multilevel Boost Converter (MBC) shows non-minimum phase behaviour. Boost converters are widely used in PV systems, fuel cells and HVDC system etc. In this paper, to regulate the output voltage duty cycle is varied and PID controller is used as duty cycle controller. PID controller shows good response in terms of settling time and also compensated the output voltage for load variation. Boost converter operates at high frequency so the size of components reduces and the ripples also reduces.